Environmental and landscape influences on the spatial and temporal distribution of a cattle herd in a South Texas rangeland - Christopher Cheleuitte-Nieves; Humberto L. Perotto-Baldivieso; X. Ben Wu; Susan M. Cooper (Ecological Processes, 2020)
Abstract The multiple spatial and temporal parameters affecting cattle herd distribution and activity dynamics can significantly affect resource utilization but are not fully understood. The aim of this study was to determine whether current animal tracking technology and spatio-temporal analysis tools can be used to integrate multi-scale information on herd distribution patterns as a function of seasonal forage production, periods of the day, animal activity, and landscape features. Positional and activity information of 11 free-ranging cows within a 31-member herd was obtained at 5-min intervals by using GPS collars for 1 year within a 457-ha ranch in the semi-arid rangelands of South Texas. Forage biomass was calculated with satellite imagery. Spatial analysis of cattle distribution and landscape features was conducted with GIS. Herd spread was greatest during the growing season. Throughout the year, during midday, the herd showed smaller spread and greater use of shade patches than any other time of day. Cattle also aggregated under trees in winter, particularly during the night. There was no statistically significant overall pattern of seasonal changes in the use of water and supplemental feeding areas, but a trend toward highest use during the winter. However, significantly different diurnal patterns in the use of supplemental feed and water were observed within each season. This study found a strong influence of shade patches relative to the influence of water and supplemental feeding areas on the diurnal and seasonal movement patterns of cattle in shrub-dominated rangeland. Although this study used only 11 tracked cows in a 31-member herd, the results indicated that techniques such as seasonal and diurnal GPS tracking, GIS, and remote sensing data enable evaluation of multiple spatial and temporal dynamics of cattle distribution and activity patterns. The smaller spread during the dry winter season associated with the observed aggregation of individuals in water and supplemental feeding areas, may aid in determining the most critical times for providing supplemental resources and guide the allocation of those resources to areas not frequently used by cattle, thus stimulating the animals to visit unused sites during the non-growing season.